Narratives of Learning: The Personal Portfolio in the Portfolio Approach to Teaching and Learning - Leslie, Paul; Camargo-Borges, Celiane (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This paper will explore how a portfolio approach to teaching and learning can help the educator incorporate unique forms of reflective practice into his or her daily work. By being able to express ideas more clearly to himself, the educator can better promote the relational construction of knowledge in his educational communities. This paper, as part of a larger body of research asks, how can a portfolio approach to teaching and learning help the educator develop unique forms of reflective practice that will help him express his ideas more clearly, first to himself and then secondly to his educational communities? Research methodology is primarily participatory action research and includes an autoethnographic review of the author’s work, reviews, interviews, observations, and focus groups with student teachers and professional teachers in the United Arab Emirates. The research concludes that in consideration of McLuhan’s (1964) notion that the “medium is the message,” the interactions that arise through the use of new media tools can lead us to relational, co-constructed ideas that are not those simply passed on from other texts. By making our thinking visible, the portfolio approach allows the educator to capture the contextual relationship between the author, the audience or community, and the knowledge being created.